PSYCHOLOGICAL ASPECTS OF AGGRESSIVE BEHAVIOR IN ADOLESCENTS (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2023)
The largest group of young people in our society are our teenagers. When teenagers have enough information about their psychological abilities, achievements, and shortcomings, they can easily overcome any setbacks in their lives, reduce their aggressive behavior in some of them, and make more use of their opportunities to be more profound, positive, and self-aware. creates ample opportunities for the formation of perceptions with inherent social value. To further expand these opportunities, we will need to organize a number of educational activities with them. One of the most pressing psychological problems facing humanity is the problem of aggressive behavior in adolescents. After all, the social development of a teenager, his activity as a person and his self-development depend in many ways on this process.